EFEKTIVITAS MODEL PEMBELAJARAN THINK TALK WRITE TERHADAP KETERAMPILAN MENULIS TEKS ULASAN DI SEKOLAH - Saidiman (Jurnal Bastra (Bahasa dan Sastra), 2024)
This research aims to describe the effectiveness of the Think Talk Write learning model on the review text writing skills of class VIII students at SMP Negeri 1 Napanokusambi. This research is classified as a quantitative type of research using experimental methods. The design used in this research is Nonequivalent Control Group Design, namely a research design using two groups selected non-randomly. Based on the results of descriptive statistical data analysis, in the minimum completeness criteria (KKM) in the control class posttest there were 9 students (39.13) who had not met the KKM standards, while 14 students (60.87) had met the KKM standards. In the experimental class posttest scores there were no students who did not meet the KKM standards. Inferential statistical analysis in the pretest normality test showed a significant value, while the posttest also showed a significant value. Both tests have a significant value above 0.05, so the students' writing results before and after being treated (Pretest-Posttest) are normally distributed. In the homogeneity test the data shows significance > 0.05 so the data is classified as homogeneous. Meanwhile, the hypothesis test also fulfilled the hypothesis assumptions which showed that Pair 1 obtained a sig value. (2-tailed) is 0.000 < 0.05, so it can be concluded that there is a difference in the average student learning outcomes for the control class pre-test and control class post-test. Meanwhile, Pair 2 obtained a sig value. (2-tailed) of 0.000 < 0.05, it can be concluded that there is a difference in the average student learning outcomes for the experimental class pre-test and experimental class post-test. The use of the Think Talk Write learning model is effective in the ability to write review texts for class VIII students at SMP Negeri 1 Napanokusambi. Keywords: Think Talk Write learning model, writing skills, review text